Protocol for generating protein profiles and distance-based network analysis of murine tissue slices - Luisa Schmidt; Philipp Antczak; Marcus Krüger (STAR Protocols)
Summary: We introduce a protocol for spatial proteomics using thin cryotome sections of mouse skeletal muscle tissue. We describe steps for preparing muscle sections and liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses to generate spatial protein profiles along the longitudinal skeletal muscle axis. We detail procedures for scanning longitudinal protein profiles and replacing missing data using a sliding window approach. This protocol has potential for applications in spatial proteomics to other tissues with asymmetric patterns such as the brain and heart tissue.For complete details on the use and execution of this protocol, please refer to Schmidt et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.